2020
DOI: 10.1038/s41377-020-00385-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial gauge field switching using orbital angular momentum modes in optical waveguides

Abstract: The discovery of artificial gauge fields controlling the dynamics of uncharged particles that otherwise elude the influence of standard electromagnetic fields has revolutionised the field of quantum simulation. Hence, developing new techniques to induce these fields is essential to boost quantum simulation of photonic structures. Here, we experimentally demonstrate the generation of an artificial gauge field in a photonic lattice by modifying the topological charge of a light beam, overcoming the need to modif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…The best-known topological ladder model is probably the Creutz ladder [17], a BDI topological insulator that also shows flat bands in a certain regime, where particles experience a self-localization phenomenon termed "Aharonov-Bohm (AB) caging" due to a magnetic flux. This effect has previously been studied in other 1D and 2D lattices, like the rhombus chain [18][19][20][21] and the T 3 and T 4 lattices [22,23], and has been observed experimentally in several setups [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The best-known topological ladder model is probably the Creutz ladder [17], a BDI topological insulator that also shows flat bands in a certain regime, where particles experience a self-localization phenomenon termed "Aharonov-Bohm (AB) caging" due to a magnetic flux. This effect has previously been studied in other 1D and 2D lattices, like the rhombus chain [18][19][20][21] and the T 3 and T 4 lattices [22,23], and has been observed experimentally in several setups [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 62%
“…Our work considers the single-particle case only, and so it is applicable for both bosonic and fermionic particles. As mentioned above, the Creutz ladder has been implemented in a cold atom system using orbitalmomentum coupling [92,93] and can be simulated in a specific regime [27] in a rhombus chain photonic lattice [27][28][29]. Recently, a Creutz ladder plaquette was also implemented in a superconducting system [94].…”
Section: Experimental Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 35 , it has been shown that artificial flux is generated in a photonic system when OAM light is injected into a waveguide lattice. Excitons in tunable lattices have recently be shown to form strongly correlated many-body phases, such as Mott insulating phases 36 or checkerboard phases 37 .…”
Section: Discussionmentioning
confidence: 99%
“…introducing topological defects in two-dimensonal structures, 10,11 applying time-dependent modulation [12][13][14] , employing synthetic modal dimensions 15 and, very recently, controlling the orbital angular momentum of the input light beam. 16 What underlies most of the observations carried out in the above systems is the first discovered and most basic consequence of the existence of gauge-fields, the Aharonov-Bohm (AB) effect 17 . The paramount importance of this effect ranges from metrological applications to basic physics 18 .…”
Section: Introductionmentioning
confidence: 99%